Pendampingan Gerakan Literasi Sekolah Kampus Mengajar 3 - Andrean Renaldy; Elfahmi Lubis; Septina Lisdayanti; Romadhona Kusuma Yudha (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The teaching campus is one of the many Merdeka Learning programs organized by the Ministry of Education and Culture. This Teaching Campus Program aims to provide solutions for 3T Elementary Schools (outermost, foremost, underdeveloped) affected by the pandemic by empowering students from various parts of Indonesia to assist teachers and principals in implementing learning activities in improving literacy, numeracy, administration, and technology in schools. The objectives of community service activities carried out by the Teaching Campus team are (1) Knowing the problem factors for the low reading interest of students at school (2) Improving the literacy culture in schools with work programs that have been made, one of which is the effort to assist the literacy movement. In this service activity, the campus teaching team at SDN 27 Central Bengkulu amounted to 6 people. The subjects appointed in this service are all students at SD Negeri 27 Bengkulu Tengah due to the low interest in reading students so that there is very little library for students to visit. The result of this community service is an increase in students' motivation to learn and read at SDN 27 Bengkulu Tengah. Thus, it is hoped that this activity will be one of the steps that can be used in building a learning spirit movement for education in Central Bengkulu in particular.